Pelatihan Public Speaking Siswa SMK Pasundan 3 Kota Cimahi untuk Mempersiapkan Karir di Dunia Kerja - Rasman Sonjaya; Almadina Rakhmaniar; M.Rizky Purnama; Moch. Fiky Trisandhi Rahmat (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
This study aims to improve the public speaking skills of vocational high school students at SMK Pasundan 3 Kota Cimahi as part of their preparation to enter the workforce. Recognizing that strong communication skills—especially in public speaking—are essential in today’s competitive job market, this program is designed to address students’ lack of confidence and limited experience in speaking in front of an audience. Through participatory and interactive training methods, students gain theoretical knowledge as well as hands-on practice in delivering speeches, managing anxiety, using body language, and composing effective presentations. The results showed a significant increase in students’ confidence and speaking skills. Participants became more responsive and adaptable in public communication situations, which are essential skills for job interviews, teamwork, and client presentations. The program also encourages the integration of communication-based extracurricular activities to ensure continued skill development. Overall, this initiative has proven effective in equipping students with the communicative competencies needed to thrive in the professional world